Ultrasonic Investigation of Molecular Interaction in Salicylic Acid Solution at Different Frequencies - Aswale, S.S.; Aswale, S.R.; Ganjare, P.J. (Asian Journal of Chemistry, 2012)
Salicylic acid is a basic nucleus used for the synthesis of different antipyretic, analgesic and antibiotic drugs which are widely used in medicinal field. Various techniques have been used to study intermolecular interactions, one such technique is the measurement of ultrasonic velocity. Ultrasonic parameters provide valuable information about various intermolecular interactions in solution. Measurements of ultrasonic velocity, density and viscosity of 0.01 M solution of salicylic acid in ethanol have been carried out at 303.15 K at different frequencies. The experimental data was used to calculate various acoustical parameters such as adiabatic compressibility (b), apparent molar compressibility (Fk), specific acoustic impedance (Z), relative association (RA), relaxation time (t) and intermolecular free length (Lf). The results are interpreted in terms of solute - solvent interactions occurring in the solution.